2020
DOI: 10.3389/fimmu.2020.567801
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-Based Strategies to Hydrolyze Gluten Peptides and Protect Intestinal Mucosa

Abstract: Gluten is a mixture of proteins highly resistant to hydrolysis, resulting in the emergence of toxic peptides responsible for gluten-related disorders. Currently, a gluten-free diet (GFD) is the unique proven therapy for celiac disease (CD). Several research groups and pharmaceutical companies are developing new nondietetic therapeutic strategies for CD. Probiotics are viable microorganisms thought to have a healthy effect on the host. The proteolytic mechanism of lactic acid bacteria comprises an extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…The increase in ELISA response after fermentation is possibly due to an increase in the number of polypeptide units with single epitopes due to gluten proteolysis/degradation. Degradation of gluten proteins by the cell envelope-associated proteinases of lactic acid bacteria present in the yogurt starter culture has been reported previously. , The increased ELISA response also suggests that the proteolytic activity accompanying 24 h of fermentation did not completely degrade all gluten proteins.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The increase in ELISA response after fermentation is possibly due to an increase in the number of polypeptide units with single epitopes due to gluten proteolysis/degradation. Degradation of gluten proteins by the cell envelope-associated proteinases of lactic acid bacteria present in the yogurt starter culture has been reported previously. , The increased ELISA response also suggests that the proteolytic activity accompanying 24 h of fermentation did not completely degrade all gluten proteins.…”
Section: Resultssupporting
confidence: 63%
“…Degradation of gluten proteins by the cell envelope-associated proteinases of lactic acid bacteria present in the yogurt starter culture has been reported previously. 38,39 The increased ELISA response also suggests that the proteolytic activity accompanying 24 h of fermentation did not completely degrade all gluten proteins.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Lactobacilli and Bifidobacterium are considered essential intestinal microbiota having beneficial effects on human health and are widely used in the formulation of probiotic products. Therapy with probiotics containing bacteria that can degrade gluten could be a possible new strategy for the complementary treatment of CeD patients [ 126 ]. Bifidobacterium species showed significant digestion of gluten protein and reduced cytotoxicity and pro-inflammatory responses [ 127 ].…”
Section: Dietary Interventions For Complementing the Gfd And Beyondmentioning
confidence: 99%
“…GM is involved in several metabolic processes and its susceptibility to the general food quality and the specific quality of wheat is well established ( 11 ). In particular, considering that GM plays a pivotal role in gut-associated immune system homeostasis, it has been demonstrated that wheat peptides, only partially digested by intestinal proteases, can have an increased or reduced immunogenicity depending on their degrading bacteria, influencing the possibility of developing wheat-related disorders ( 12 ). Another core GM activity is carbohydrate fermentation with the consequent production of short- (SCFAs) and medium-chain fatty acids (MCFAs), critical metabolites that can regulate intestinal physiology and modulate immune functions, as well as serving as energy source for colonocytes or other resident bacteria ( 13 ).…”
Section: Introductionmentioning
confidence: 99%